Changes in AZGP1 Serum Levels and Correlation With Pulse Wave Velocity After Kidney Transplantation - Kraemer, Thomas Daniel; Soerensen-Zender, Inga; Memaran, Nima; Haller, Hermann; Melk, Anette; Schmidt, Bernhard Magnus Wilhelm; Schmitt, Roland (Frontiers in Cardiovascular Medicine, 2021)
Background: Zinc-alpha 2-glycoprotein (AZGP1), a secreted protein with ubiquitous tissue expression, has been controversially linked to the risk of cardiovascular disease. In a cohort of kidney transplant recipients, we measured serum AZGP1 levels after transplantation over a two year period and tested for an association with pulse wave velocity as an important parameter indicating future cardiovascular events. Methods: Annual blood sampling and pulse wave velocity measurements were longitudinally performed in 113 kidney transplant recipients. AZGP1 was measured in serum samples using standard ELISA. Association of AZGP1 with pulse wave velocity was longitudinally assessed during follow up of two years by mixed longitudinal modelling. Results: AZGP1 serum levels declined significantly after kidney transplantation. This decline was dependent on allograft function as indicated by inverse correlation with eGFR. When corrected for eGFR multivariable analysis revealed an inverse correlation between AZGP1 and pulse wave velocity. This analysis further showed independent associations of older age, higher blood pressure, and higher calcium phosphate product with higher pulse wave velocity. Conclusions: Improved kidney function after transplantation leads to a decline in AZGP1 serum levels. Independent of kidney function and other cardiovascular risk factors lower AZGP1 levels are associated with higher pulse wave velocity in the two years after kidney transplantation. These data suggest that AZGP1 might be a potential biomarker for cardiovascular health and a target for improving cardiovascular outcome.